ANALISA INVESTASI BERLANDASAN HUKUM ISLAM - Afifah Nur Millatina; Puti Khairani Rijadi (Institut Bisnis Muhammadiyah Bekasi, 2022)
Many people still consider illegal investment activities to be the same as gambling games and so on, even though the Indonesian Ulema Council has carried out ijtihad and Ijma for good investment activities, starting from mutual funds, stocks, and so on. This research will examine all legal aspects regarding investment, the risks faced solutions to avoid investment risks, and so on in accordance with Islamic Sharia laws (Al-Qur'an, Al Hadith, Ijma, and Qiyas). and in investing, of course doing various things including analysis, so this research will discuss how to carry out an analysis of investments in accordance with Islamic law permissible (Al Qur'an, Al Hadst, Ijma, and Qiyas). This research was carried out from various literature and experiences of investors who have tasted a lot of sweetness and bitterness in the investment world. In the current era, there are very many investments that are lured to get 100% results in a short time, basically investing has a process and is not always profitable or even detrimental. This research will discuss dealing with all aspects of society that are deceived by fraudulent investments by theFinancial Services Authority.